Productive performance and economics of Tellicherry buck kids fed varying levels of hydroponic maize fodder - JEMIMAH, E RACHEL; GNANARAJ, P TENSINGH; SIVAKUMAR, T; GOPINATHAN, A; SUNDARAM, S MEENAKSHI (The Indian Journal of Animal Sciences, 2022)
The present work was carried out to study the growth performance and economics of Tellicherry buck kids fed varying levels of hydroponic maize fodder. Tellicherry buck kids (24) were divided into three groups and fed with diets consisting of 100% concentrate, 75% concentrate + 25% hydroponic maize fodder and 50% concentrate + 50% hydroponic maize fodder respectively. Kids supplemented with hydroponic maize fodder replacing concentrate at 25% and 50% level had numerically higher overall weight gain, average daily gain, final body weight and lower cost of production/kg live weight gain (`) than 100% concentrate fed kids. From the study, it can be concluded that the concentrate can be replaced with hydroponic maize fodder at 25% and 50% levels in the diets of Tellicherry buck kids for better growth and profit.